Development of the quality of personnel work life in Samutsakhon Provincial Administration Organization - Sasingh, Nattawan (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aimed at (1) studying of personnel’s background affecting the quality of work life in Samutsakhon Provincial Administration Organization; (2) comparing relationship of the development of the quality of personnel work life in Samutsakhon Provincial Administration Organization including performance in duty, work quality and understanding in the operation; and (3) studying problems and obstacles that occurring and proposes guidelines for solving those problems and obstacles in the development of the quality of personnel work life in Samutsakhon Provincial Administration Organization. The samples included 120 personnel who work for Samutsakhon Provincial Administration Organization. A questionnaire was used for collecting data and the statistics analyze included frequency, percentage, mean, standard deviation and hypothesis testing used t-test and F-test at statistical significance of .05 and .001 and correlation coefficient. The findings indicated that: 1. The personnel’s background affecting the quality of work life in Samutsakhon Provincial Administration Organization; the most of respondents were 80 female; the 59 people have aged between 30 to 40 years old, representing of 49.1 percent; the 98 people graduated in bachelor degree, representing of 81.7 percent; the 109 people have marital status, representing of 90.8 percent; the 51 people who have timing of work between 11 to 20 years, representing of 42.5 percent and the 57 people have income per a month between 15,001 to 20,000 Baht, representing of 47.5 percent. The overall of development of the quality of personnel work life in Samutsakhon Provincial Administration Organization at ( ) = 3.07; their opinions were uncertainty. In considering in question found that; the most of high average was performance in duty at ( ) = 3.38; their opinions were uncertainty; performance in quality development that added value in the profession at ( ) = 3.26 and the least average at ( ) = 2.85 included participation of organization that uncertainty. 2. The hypothesis testing of comparing relationship of the development of the quality of personnel work life in Samutsakhon Provincial Administration Organization showed that; (2.1) the difference of success of personnel work with background of education; their opinions of relationship of the development of the quality of personnel work life in Samutsakhon Provincial Administration Organization at statistically significance level of .05. The level of gender, marital status, timing of work and income per a month was not difference at statistically significance level of .05. (2.2) the characteristic of work with background of gender, marital status, timing of work and income per a month; their opinions of the development of the quality of personnel work life in Samutsakhon Provincial Administration Organization was not difference at statistically significance level of .05. (2.3) the understanding of work with background of gender, marital status, timing of work and income per a month; their opinions of the development of the quality of personnel work life in Samutsakhon Provincial Administration Organization was not difference at statistically significance level of .05. There should be more support of the quality of personnel work life in Samutsakhon Provincial Administration Organization with encourage further study to increase existing knowledge in order to be used in performing their duties efficiently while attending training, seminar to increase knowledge regularly for the improvement of quality of life in order to build morale in the operations for personnel in Samutsakhon Provincial Administration Organization. Article history : Received 1 February 2019 Revised 6 Mar 2019 Accepted 8 Mar 2019 SIMILARITY INDEX = 3.59